An investigation of the foot ankle joint mobility, muscle strength, and foot structure in adolescent with type 1 diabetes - Mutlu, Ebru Kaya; Unver, Banu; Taskiran, Hanifegul; Ozgen, Ilker Tolga; ÖZGEN, İLKER TOLGA (My University, 2018)
Muscle strength and joint mobility were decreased with type 1 diabetes mellitus (T1DM). However, the literature is limited about foot muscle strength, joint mobility, and structure in adolescent aged 13-17 with T1DM. The purpose of this study was to compare foot structure, muscle strength, and joint mobility of adolescents aged between 13 and 17 with T1DM to those of healthy adolescents. Cross-sectional study design including adolescents with T1DM aged 13-17 years, and healthy adolescents was used in the study. The range of motion (ROM) was measured by using a digital goniometer, and muscle strength was evaluated by using handheld-dynamometry. Footprint was used for foot structure. Assessments were performed by using the digital images, and Clarke-s angle (CA), Staheli Arch index (SAI), and Chippaux-Smirak index (CSI) were calculated by using a scientific image-analysis program, ImageJ. Forty-one T1DM and 28 healthy adolescents were included with a mean age of 15.29 +/- 1.55 and 15.04 +/- 1.42, respectively. The T1DM group had significantly lower dorsiflexion, inversion and eversion ROM, and lower tibialis anterior and gastrocnemius muscle test (p 0.05). Adolescents with T1DM have lower ankle and foot joint mobility and muscle strength and altered foot structure compared to their healthy contemporaries. This indicates that early screening of muscle strength and foot structure are important to determine and avoid various risks such as foot deformities, gait deviations, and ulcer.